Investigations of CdS and Ag-CdS nanoparticles by X-ray photoelectron spectroscopy - Thakur, Priya; Joshi, Satyawati S.; Patil, K. R. (Applied Surface Science, 2010)
In the present report, CdS and Ag-CdS nanoparticles were synthesized using cysteine as a capping agent. Surface properties CdS and Ag-CdS nanoparticles were studied by X-ray photoelectron spectroscopy (XPS). XPS study of CdS nanoparticles was carried out as a function of pH and for a refluxed sample at pH 11.2. Effect of dopant concentration on surface properties of Ag-CdS nanoparticles was also studied for as prepared samples as well as for annealed sample at 2% doping. Effect of pH, dopant concentration, and effect of particle size on different sulfur species present in the system was studied. Features of Cd 3d, S 2p and Ag 3d core level have been discussed in detail. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ag-CdS; CdS; Cysteine; XPS